Influence of spawning stock size and environment on abundance and survival of juveniles in commercially important fish stocks in the Barents Sea - Dingsør, Gjert Endre (Fisheries Research, 2006)
Stock-recruitment relationships are fundamental in management of fish stocks and fish recruitment is highly variable. Hence, a mechanistic understanding of the factors causing the variability in recruitment is a necessity to be able to predict the development of a harvestable stock. To get continuity in the management it is also important to get an early indication of the size of future year-classes recruiting to the fisheries. Survey-based abundance indices are often used to assess the state of a fish stock and to predict the strength of future year-classes, it is therefore important that these estimates give a correct picture of the present state of the stock. However, both biotic and climatic factors are known to affect year-class strengths and these factors can exhibit nonlinearities and non-additive properties that are difficult to incorporate in traditional stock-recruitment models. My thesis consists of three papers focusing on I) estimation of abundance indices of 0-group fish in the Barents Sea, II) biotic and climatic effects on 0-group and age-1 abundances of capelin (Mallotus villosus), northeast Arctic cod (Gadus morhua), northeast Arctic haddock (Melanogrammus aeglefinus), and Norwegian spring spawning herring (Clupea harengus), and III) spatial variability in survival of 0-group northeast Arctic cod. Survey data of 0-group fish in the Barents Sea are reviewed back to 1980, new abundance indices are estimated, and different methods for estimating abundance indices are evaluated. The new methods used to calculate the indices retain more of the dynamics in the annual recruitment than the previous methods do. The Pennington estimator method is concluded to be the preferable method for estimating 0-group indices for the Barents Sea. It is also attempted to correct for lengthdependent selection properties of the trawl and it is shown that this bias affects both length and abundance estimates. However, it is concluded that more research is needed to quantify this bias under different environmental ...